High-Resolution Sonography of the Peripheral Nervous System - Peer, Siegfried; Bodner, Gerd (Diagnostic Imaging,, 2008)
Since the first edition of this book, sonography of the peripheral nervous system has evolved further. Not only has knowledge of the sonographic features of common neurological disorders deepened, but constant research has led to the application of sonography in the diagnosis and guided treatment of disorders that were not previously accessible. This second, revised edition reflects these ongoing developments in various ways: many state of the art high-resolution images are included, the text has been adapted to reflect the current state of the literature, and information is presented using a more modern layout. Anatomic/sonographic correlation is considered in depth, and examination technique with modern sonography equipment is explained. This book provides a practical, clinically oriented overview of all aspects of sonographic diagnosis and interventional therapy of the peripheral nervous system and will be of value to all with an interest in this field.